2010
DOI: 10.1590/s1806-83242010000400002
|View full text |Cite
|
Sign up to set email alerts
|

A novel bioactive glass-ceramic for treating dentin hypersensitivity

Abstract: Dentin hypersensitivity (DH) is a painful response to stimulus applied to the open dentinal tubules of a vital tooth. It's a common oral condition, however, without an ideal treatment available yet. This work evaluated in vitro the effect of micron-sized particles from a novel bioactive glass-ceramic (Biosilicate) in occluding open dentinal tubules. A dentin disc model was employed to observe comparatively, using scanning electron microscopy (SEM), dentinal tubule occlusion by different products and deposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0
19

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 11 publications
0
74
0
19
Order By: Relevance
“…Several treatment modalities and agents have been used in the management and resolution of dentin hypersensitivity, but their efficacy has varied from one study to another and it is not yet established in the literature (2,15,(20)(21)(22)(23). Further research is needed to clarify the mechanisms and etiology of this uncomfortable clinical condition.…”
Section: Discussionmentioning
confidence: 99%
“…Several treatment modalities and agents have been used in the management and resolution of dentin hypersensitivity, but their efficacy has varied from one study to another and it is not yet established in the literature (2,15,(20)(21)(22)(23). Further research is needed to clarify the mechanisms and etiology of this uncomfortable clinical condition.…”
Section: Discussionmentioning
confidence: 99%
“…Biosilicate® is among the derivatives of bioglasses with the original formulation (Na 2 -CaO-SiO 2 -P 2 O 5 ), but it also contains Li 2 O and K 2 O [18], and in nanoparticulate form (0.1 to 10 μm) in 10% solution, it was found to promote the obliteration of dentinal tubules when in contact with dentin for 24 hours [19]. Microscopic and spectrophotometric analysis suggested the formation of an adhesive layer of hydroxyapatite on the dentin surface that is hypothetically responsible for the permanent obliteration of dentinal tubules [20].…”
Section: Discussionmentioning
confidence: 99%
“…The fluoride gel was applied using a micro-applicator for 1 min on the exposed dentin surface. For bioactive material, a mixture of 0.100 g of powder with 1 mL of distilled water (1:10 ratio) was applied for 5 minutes 22,24 . Group 2 (G2): fluoride gel and nanostructured desensitizing (Desensibilize Nano P; FGM Dental Materials, Joinville, SC, Brazil).…”
Section: Methodsmentioning
confidence: 99%
“…This change results in particles with lower cutting potential and proven biological properties 20,21 , reducing dentin hypersensitivity 22 . Previous studies have shown that, after biosilicate application on the dentin, deposition of hydroxycarbonate apatite in open dentinal tubules was observed, forming a uniform layer over this surface 23,24 .…”
Section: Introductionmentioning
confidence: 99%